PERBANDINGAN BIAYA ANTARA PERKERASAN ASPAL DAN KONSTRUKSI INTERBLOK - Rano Laurent (Jurnal Teknologi Berkelanjutan, 2019)
Considering the high cost of maintaining asphalt pavement, we need an alternative that is able to provide optimal results and economic costs, in this case using interlocking pavement construction. Interlocking construction pavement has several advantages from asphalt pavement, including being able to be done manually so that construction and road maintenance costs can be reduced. The purpose of this research is to study the design of asphalt pavement thickness and interblock construction using the AASHTO '93 method. The analysis methods were to calculate the construction costs of each pavement, to prepare maintenance cost scenarios and to conduct an economic analysis over the life of the plan to determine the economic type of pavement. The results showed that the research road section with a length of 285 m and a width of 20 m with a W18 value of 12,714,787.73 SS obtained asphalt pavement thickness used was 10 cm for the surface layer, 15 cm for the foundation layer and without using the bottom foundation layer , while in the interlocking pavement construction, the thickness used is 10 cm for paving and 5 cm for base sand (surface layer), 15 cm for the foundation layer and without using the bottom foundation layer. Construction and maintenance costs for 20 years for both types of pavement are Rp. 691,580,145.00 for asphalt pavement and Rp. 567,160,545.00 for inter-block pavement construction, this shows that asphalt pavement is 18% more expensive compared to inter-block pavement so that inter-block pavement is more economical to use for pavement used as container traffic.